Effects of light irradiation upon photodynamic therapy based on 5-aminolevulinic acid–gold nanoparticle conjugates in K562 cells via singlet oxygen generation - Xu, Hao (Dove Medical Press, 2012)
PURPOSE: As a precursor of the potent photosensitizer protoporphyrin IX (PpIX), 5-aminolevulinic acid (5-ALA), was conjugated onto cationic gold nanoparticles (GNPs) to improve the efficacy of photodynamic therapy (PDT). METHODS: Cationic GNPs reduced by branched polyethyleneimine and 5-ALA were conjugated onto the cationic GNPs by creating an electrostatic interaction at physiological pH. The efficacy of ALA-GNP conjugates in PDT was investigated under irradiation with a mercury lamp (central wavelength of 395 nm) and three types of light-emitting diode arrays (central wavelengths of 399, 502, and 621 nm, respectively). The impacts of GNPs on PDT were then analyzed by measuring the intracellular PpIX levels in K562 cells and the singlet oxygen yield of PpIX under irradiation. RESULTS: The 2 mM ALA-GNP conjugates showed greater cytotoxicity against K562 cells than ALA alone. Light-emitting diode (505 nm) irradiation of the conjugates caused a level of K562 cell destruction similar to that with irradiation by a mercury lamp, although it had no adverse effects on drug-free control cells. These results may be attributed to the singlet oxygen yield of PpIX, which can be enhanced by GNPs. CONCLUSION: Under irradiation with a suitable light source, ALA-GNP conjugates can effectively destroy K562 cells. The technique offers a new strategy of PDT.